1981
DOI: 10.2135/cropsci1981.0011183x002100020007x
|View full text |Cite
|
Sign up to set email alerts
|

Root Characteristics of 44 Maize Inbreds Evaluated in Four Environments1

Abstract: To study root characteristics, as well as potential tolerance to corn rootworms (Diabrotica spp.) of northern‐adapted genotypes, 44 maize (Zea mays L.) inbreds were evaluated at two locations in both 1974 and 1975 for vertical‐pull resistance at the pretassel and kernel milk stages of plant growth and, for root dry weight and root spread at the later growth stage. The inbreds also were evaluated at one location in 1975 for root‐rot resistance at the kernel dent stage of growth to determine its effect on pull r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Zaidi et al (2003) found that for most physiological traits and yield the correlation between maize parents and their crosses increased under low N. If so, then the performance of high generation inbreds under multi-level N supplies can be used to predict the performance of the hybrids. Betra´n et al (2003) also found a significant positive correlation between the hybrid and mid-parent grain yield under both high and low N conditions, with increased correlation under low N. A number of experiments have shown significant genetic variation in the root characteristics and architecture of maize (Hebert et al, 1992;Jenison et al, 1981;Landi et al, 1998). Some quantitative trait loci (QTLs) for root traits in maize have also been identified (Tuberosa et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Zaidi et al (2003) found that for most physiological traits and yield the correlation between maize parents and their crosses increased under low N. If so, then the performance of high generation inbreds under multi-level N supplies can be used to predict the performance of the hybrids. Betra´n et al (2003) also found a significant positive correlation between the hybrid and mid-parent grain yield under both high and low N conditions, with increased correlation under low N. A number of experiments have shown significant genetic variation in the root characteristics and architecture of maize (Hebert et al, 1992;Jenison et al, 1981;Landi et al, 1998). Some quantitative trait loci (QTLs) for root traits in maize have also been identified (Tuberosa et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…In the following years, a few inbred lines with improved resistance to corn rootworm larval feeding were developed (37). These lines were characterized by large, densely branched root systems and the ability for quick root regeneration after corn rootworm injury.…”
Section: Biological Control and Host Plant Resistance: Realistic Manamentioning
confidence: 99%
“…The efficiency of selection for yield in low-P environment may be improved by selecting Pcorrelated traits. The traits related to efficient P uptake and metabolism have been suggested as selection parameters (Hinsinger 2001;Jenison et al 1981). Plants can actively improve their acquisition of P in several ways.…”
Section: Introductionmentioning
confidence: 99%